Active Noise Cancellation for Underwater Environment Using Raspberry Pi - Nanang Syahroni; Widya Andi P; Hari Wahjuningrat S; R Henggar B (IC-ITECHS, 2014)
Noise can interfere activities both on land and in the underwater environment. In this paper we propose a noise cancellation system using ANC (Active Noise Control) techniques to reduce acoustic noise signal using Raspberry Pi, to receive an amplitude and phase of the noise signal, calculate each sampled signal using normalised least means square (NLMS), and finally it will produce a replica of the transmitled noise by shifting the phase noise at 180°, through the speaker in real-time environment so that the signal noise can be reduced and decrease. The system is designed using Matlab and Simulink, the model is compiled for Raspberry Pi board as the hardware target. Raspberry Pi is a small computer so it make a system more efficient. The experimentation results shows that ANC can work in an optimal mode in delay=5 and filter length=64 and can reduce noise level until 0,894 dB in underwater environment and maximal reduction level in 2 Khz frequency. The system can influence in around the system and reduce the signal level about 1,97 dB in 10 cm depth, and 1,02 dB in 40 cm depth.